Energy Homeostasis Control in Drosophila Adipokinetic Hormone Mutants. Issue 2 (14th August 2015) - Gáliková, Martina; Diesner, Max; Klepsatel, Peter; Hehlert, Philip; Xu, Yanjun; Bickmeyer, Iris; Predel, Reinhard; Kühnlein, Ronald P
Abstract: Maintenance of biological functions under negative energy balance depends on mobilization of storage lipids and carbohydrates in animals. In mammals, glucagon and glucocorticoid signaling mobilizes energy reserves, whereas adipokinetic hormones (AKHs) play a homologous role in insects. Numerous studies based on AKH injections and correlative studies in a broad range of insect species established the view that AKH acts as master regulator of energy mobilization during development, reproduction, and stress. In contrast to AKH, the second peptide, which is processed from the Akh encoded prohormone [termed "adipokinetic hormone precursor-related peptide" (APRP)] is functionally orphan. APRP is discussed as ecdysiotropic hormone or as scaffold peptide during AKH prohormone processing. However, as in the case of AKH, final evidence for APRP functions requires genetic mutant analysis. Here we employed CRISPR/Cas9-mediated genome engineering to create AKH and AKH plus APRP-specific mutants in the model insect Drosophila melanogaster . Lack of APRP did not affect any of the tested steroid-dependent processes. Similarly, Drosophila AKH signaling is dispensable for ontogenesis, locomotion, oogenesis, and homeostasis of lipid or carbohydrate storage until up to the end of metamorphosis. During adulthood, however, AKH regulates body fat content and the hemolymph sugar level as well as nutritional and oxidative stress responses. Finally, we provide evidence for a negative autoregulatory loop in Akh gene regulation.